2003
DOI: 10.1002/pssb.200301703
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction study of crystal and magnetic structure of (La0.7Ca0.3)1–xMn1+xO3 (x = 0, 0.1) systems

Abstract: PACS 75.25.+z, 75.50.Dd The evolution of crystal and magnetic structures of (La 0.7 Ca 0.3 ) 1-x Mn 1+x O 3 (x = 0, 0.1) as a function of temperature was determined. For both compounds the crystal structure is orthorhombic (space group Pnma) with the following sequence of the lattice constants: b/ 2 < a < c for x = 0 and c < a < b/ 2 for x = 0.1. The para-ferromagnetic transitions at T c = 265 K for x = 0 and 260 K for x = 0.1 are accompanied by structural distortions. For x = 0 the ferromagnetic ordering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A strong influence of manganese excess on magnetic properties and resonance has been established both in La-Ca manganites [24][25][26][27] and in self-doping manganites [28]. The main results of the cited references are as follows: using the NMR method it was shown that the manganese ions with ionization states both close to (3+) and (4+) and with intermediate valence result from the high-frequency electron exchange; FM-to-canted spin state transition in clusters of multivalent Mn ions by magnetic and neutron measurements was observed; observation of FMR and spin-wave resonance in the films of manganites with manganese excess.…”
Section: Introductionmentioning
confidence: 99%
“…A strong influence of manganese excess on magnetic properties and resonance has been established both in La-Ca manganites [24][25][26][27] and in self-doping manganites [28]. The main results of the cited references are as follows: using the NMR method it was shown that the manganese ions with ionization states both close to (3+) and (4+) and with intermediate valence result from the high-frequency electron exchange; FM-to-canted spin state transition in clusters of multivalent Mn ions by magnetic and neutron measurements was observed; observation of FMR and spin-wave resonance in the films of manganites with manganese excess.…”
Section: Introductionmentioning
confidence: 99%